2020
DOI: 10.1063/5.0002168
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced magnetization in proton irradiated Mn3Si2Te6 van der Waals crystals

Abstract: Van der Waals (vdWs) crystals have attracted a great deal of scientific attention due to their interesting physical properties and widespread practical applications. Among all, CrSiTe3 (CST) is a ferromagnetic semiconductor with the Curie temperature (TC) of ~32 K. In this letter, we study the magnetic properties of bulk CST single crystal upon proton irradiation with the fluence of 1×10 18 protons/cm 2 . Most significantly, we observed an enhancement (23%) in the saturation magnetization from 3.9 µB to 4.8 µB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
(79 reference statements)
1
8
0
Order By: Relevance
“…The synthesis of mm-sized CST crystals was conducted as previously reported with the self-flux method starting with Cr powder and Si and Te pieces [18]. The crystals were then irradiated with a 2 MeV proton beam in 1.7 MV Tandetron Accelerator following closely the procedure discussed in [6][7][8][9]. The energy of the beam is kept low enough to avoid damage to the crystal.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis of mm-sized CST crystals was conducted as previously reported with the self-flux method starting with Cr powder and Si and Te pieces [18]. The crystals were then irradiated with a 2 MeV proton beam in 1.7 MV Tandetron Accelerator following closely the procedure discussed in [6][7][8][9]. The energy of the beam is kept low enough to avoid damage to the crystal.…”
Section: Methodsmentioning
confidence: 99%
“…It was also reported that there is an exotic quantum state driven by ab plane chiral orbital currents in Mn 3 Si 2 Te 6 [12]. These intriguing features have inspired a lot of research works to unearth the electronic and magnetic properties of Mn 3 Si 2 Te 6 [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, external stimuli have been employed to tune the magnetic states in quasi-2D materials via photoexcitation, proton irradiation, strain, gating, doping, pressure, and intercalation. Among all, hydrostatic pressure has been used as a disorderless procedure to tune the physical properties of vdW compounds. Pressure on a system of weakly coupled layers affects the bonding and interlayer coupling without destroying the crystal .…”
Section: Introductionmentioning
confidence: 99%